Pengaruh Pengungkapan ESG, Financial Leverage, Operating Leverage Terhadap Risiko Sistematis - Aisyah Maharani; Christina Dwi Astuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of corporate sustainability, financial leverage, operating leverage on systematic risk. This research uses quantitative methods. The data used is ESG scores and financial reports available on the Indonesian Stock Exchange. The samples used in this study are company that listed on ESGL Index in period quartal 1st in 2021 until quartal 1st in 2023. Data were collected using purposive sampling. The total number of sample in this study is 46 companies with 9 period quartals, resulted 197 data. The result of the study using liniear regression analysis indicate that financial leverage has a positive effect on systematic risk. Then the results of linier regression analysis indicate that operational leverage and esg disclosure doesn't have any effect on systematic risk. Keywords: Systematic Risk, Esg Disclosure; Financial Leverage; Operating Leverage